Satisfaction with a therapeutic sleeve for arm lymphedema secondary to breast cancer treatment: Controlled crossover trial - Osório, F (2017)
Secondary arm lymphedema is a feared late iatrogenic side effect of breast cancer survivors with a negative impact on patient's self-image and quality of life. Its reported incidence is extremely variable, from 6% to 80%, as well as the effectiveness of the multimodal decongestive lymphedema therapy. In their daily life breast cancer survivors with lymphedema have few alternatives but to use a compressive sleeve. Concerned with the well-known low compliance to the daily use of traditional sleeves, we conducted a comparative study in a subgroup of our patients with lymphedema secondary to breast cancer treatment for the subjective assessment of PRADEX®, an innovative class 1 compression sleeve. Secondarily, we aimed to assess the non-inferiority of PRADEX® regarding subjective and objective measures of the severity of lymphedema. We studied 46 women with grade 1 secondary arm lymphedema, who used their usual sleeve and PRADEX® daily for 2 weeks each, in a crossover design. The new therapeutic sleeve was classified as having a better design and a better usability and comfort (more comfortable, thinner, fresher, softer, more flexible, comfortable, resistant to dirt and easier to dress and to wear). Women's subjective opinion about the severity of lymphedema favored their usual sleeve in detriment of PRADEX®, but this subjective feeling was contradicted by objective measurements of different perimeters of the arm at the beginning and at the end of the study. We concluded that the PRADEX® sleeve, not being worse in its compressive therapeutic efficacy, is much better with regard to patient comfort.